2014
DOI: 10.1080/02626667.2013.822642
|View full text |Cite
|
Sign up to set email alerts
|

Application of a tank model to assess the flood-control function of a terraced paddy field

Abstract: Terraced paddy fields play a crucial role in water and soil conservation because their water-storage capacity reduces flood peaks in mountainous areas. The water-storage capacity of a paddy field is mainly dependent on the size of the field, the height of the bund, and the outlet within the bund. However, the height of the bund and outlet can be reduced due to a lack of maintenance, especially when rice paddies have been abandoned. This study assessed the flood-control function of a terraced paddy field during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Thus, parameter calibration can be challenging, especially when streamflow observations are limited [36,37]. The models have been widely used in East Asia, including Korea, Japan, and Taiwan, and studies have demonstrated their accuracy and performance in applications for humid and mountainous watersheds [8,9,17,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, parameter calibration can be challenging, especially when streamflow observations are limited [36,37]. The models have been widely used in East Asia, including Korea, Japan, and Taiwan, and studies have demonstrated their accuracy and performance in applications for humid and mountainous watersheds [8,9,17,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual Tank model was adopted to simulate the rainfall-runoff processes, thus providing the behavior of rainwater in surface runoff, soil infiltration, and seepage [33][34][35]. The Tank model describes the amount of water storage in a watershed with a series of tanks with the outlets on the side and bottom of the tanks [36].…”
Section: Hydrological Modelmentioning
confidence: 99%
“…However, these terraces can be used as alternatives when bench terrace construction is not convenient on steep slopes (Zheng and Zhang, 2001;He et al, 2008). The benefits of terracing on the control of water erosion are also influenced by the size and shape of the platform, the height of the embankment, and the outlet within the bund (Dorren and Rey, 2004;Chen et al, 2014). The dimensions of level terraces are determined based on the surface runoff volume, and the sizes of sloped and zig terraces are based on the maximum runoff flow rate.…”
Section: Sediment Reductionmentioning
confidence: 99%